Participants' evaluation of an internet-based group compassion-focused therapy program for young people in Sweden - Vestin, Magnus; Jokinen, Jussi; Blomqvist, Ida; Dennhag, Inga (Frontiers in Psychology, 2025)
IntroductionOnline group compassion-focused therapy (CFT) has not been thoroughly studied in young people, and the participants' perspectives on the treatment are highly relevant.MethodsA seven-session internet-based group CFT program was evaluated for young people aged 15–20 (n = 42, females = 37). A self-report evaluation questionnaire, specifically designed for this study, was administered post-intervention. The current study investigated: (1) Potential factors influencing the treatment program goals (increase self-compassion, reduce self-criticism and increase affect-regulation abilities) and the participants' overall experience of the treatment; and (2) The effect each intervention exercise had on the program goals according to the participants' ratings.ResultsParticipants generally reported high satisfaction and had a high attendance rate. Only 2.4% of the participants completed less than half of the sessions and 71% of the participants attended at least six of the seven sessions. Exercises that integrated traditional cognitive-behavioral therapy (CBT) and Compassion-Focused Therapy (CFT) principles received high ratings, whereas breathing and mindfulness exercises were rated lower in many cases. Several compassion exercises were also highly rated, such as the Threat-drive and security system, based on CFT affect-regulation theory. The majority did not find home assignments helpful.DiscussionThe findings suggest that internet-based group CFT could be an easily accessible and acceptable intervention for young people in primary care, though further research is warranted.